Comparison of Artificial Intelligence with other interventions to improve Adenoma Detection Rate for Colonoscopy: : A Network Meta-analysis - Aziz, Muhammad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.